Comment : battling the drug trade. - COWAL, Sally (1994)
The US Ambassador to Trinidad and Tobago expresses her concerns and appreciations of the relationship between the US government and the government of Trinidad and Tobago with respect to cooperation in the battle against illicit drugs.